Studi Fenomenologi Dampak Kemiskinan Terhadap Motivasi Sekolah Anak Pesisir di Desa Pliwetan - Adriel Fabian Cannavaro; Dzulfikar Akbar Romadlon (Jurnal Perspektif, 2023)
The economic conditions of the parents of children at both the elementary and high school levels in Pliwetan Village varied, starting from the lower, middle and upper economic levels. this makes the economic conditions of parents do not have a significant effect on children's motivation to study at school. This research aims to find out how the impact of poverty on children's learning motivation. The method used in this study is a qualitative research method with a phenomenological approach. The results of the study showed that most parents in Pliwetan village, Palang sub-district, belonged to the lower middle category, so that the role of parents towards their children was not fulfilled. Therefore, the impact of parents' economic conditions makes children participate in helping the family economy so that this affects children's learning motivation at school.